KONSEP PENDIDIKAN AKHLAK ANAK DALAM ISLAM (STUDI ANALISIS KITAB TAISIRUL KHOLLAQ KARYA AL-HAFIZH HASAN AL-MAS’UUDI) - Hardianto, Mujib; Syamsuddin, Syamsuddin (Al-Misbah (Jurnal Islamic Studies), 2020)
Moral education is given to guide and educate children in order to achieve their life goals, namely to grow their awareness as human beings as creatures of Allah. in order to have good morals, now moral education is considered very important. With the book Taisirul Khollaq explained clearly the problem of morality. As for the focus of research in this study, namely: 1. What is the concept of child moral education in Islam? 2. What is the concept of children's moral education in the Taisirul Khollaq book? This research uses the type of library research (library research). The approach in this study is a descriptive analysis approach. As for the results of the analysis I got in this study, that the concept of children's moral education in the book Taisirul Khollaq is the character of Allah SWT. Praised and despicable morals, praiseworthy ie praiseworthy deeds and words that flow without feeling forced out of oneself. Praiseworthy among others; honest, trustworthy, generous, generous, humble, fair, and others. While despicable morals are despicable actions and words that flow by feeling forced out of oneself. Despicable among others; lying, revenge, hasud, gossiping, fighting sheep, arrogant, dhalim, and others. This research is expected to bring benefits so that everyone can have good morals.